Effects of sampling techniques on population assessment of invasive round goby Neogobiusmelanostomus. Issue 6 (13th May 2013) - Brandner, J.; Pander, J.; Mueller, M.; Cerwenka, A. F.; Geist, J.
<x xml:space="preserve">Abstract</x> In this study, a comparison of point abundance sampling (PAS) electrofishing, angling with two different hook sizes and trap‐based fishing was performed in a non‐wadeable river to analyse their effects on catch per unit effort (CPUE) and population characteristics of invasive round goby Neogobius melanostomus. PAS electrofishing was identified as the most effective (mean ± s.e. CPUE = 57 ± 4 N. melanostomus min−1) and least selective method in terms of size, feeding status and species composition. Angling had the second highest CPUE, but was more size selective and resulted in a higher proportion of males compared to electrofishing [overall sex ratio angling (female:male) = 1:0·92, electrofishing 1:0·65]. Owing to low CPUE (0·012 ± 0·004) and low frequency of occurrence, minnow traps were least suitable for N. melanostomus population assessment. The results of this study suggest that a higher degree of standardization and inter‐calibration is useful to achieve better comparability of population data of invasive N. melanostomus and other benthic fish species.